26.8k views
4 votes
Consider the equation x +1 = 2.

Rewrite the equation by multiplying both sides by x +1
DO NOT USE A MULTIPLICATION SYMBOL​

User Labibah
by
5.1k points

2 Answers

1 vote

Answer:

x² + 2x + 1 = 2x + 2

Explanation:

Multiply without the multiplication symbol so use distributive property.

(x+1)(x+1) = 2(x+1)

Use the FOIL method (first, outer, inner, last)

(x)(x)+(x)(1)+(1)(x)+(1)(1) = (2)(x)+(1)(2)

which will give you:

x²+x+x+1 = 2x+2

combine like terms

x²+2x+1 = 2x+2

ta da! hope this helps

User Ondrej Sika
by
4.9k points
3 votes

Answer:

x^2 + 2x +1 = 2x + 2

Explanation:

(x+1) = 2

multiplying both sides by x +1

(x +1) (x+1) = 2 (x+1)

x^2 + 2x +1 = 2x + 2

User Rosejn
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.